Robert Morris papers - Morris, Robert, 1734-1806.
Correspondence, letterbooks, journals and proceedings of the Continental Congress, accounts, and other papers. Most of the public papers relate to the financing of the American government and its forces during the Revolution. Includes the account rendered by Pierre Augustin Caron de Beaumarchais to Congress in 1782, copies of Morris's official letters, and his private business papers such as correspondence of the Philadelphia shipping firm of Willing, Morris & Company.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Superintendent of finance for the Continental Congress during the Revolution, merchant, land speculator, and statesman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
One letter (1778) was previously cataloged separately as part of the Miscellaneous Manuscripts collection.
Keywords: Beaumarchais, Pierre Augustin Caron de, -- 1732-1799.; United States. -- Continental Congress; Willing, Morris & Company -- Correspondence; Finance, Public -- United States -- History -- To 1789.; United States -- History -- Revolution, 1775-1783 -- Finance; Land speculators; Merchants; Public officials; Statesmen